2007
DOI: 10.1007/s10865-007-9108-5
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of Blame, Self-forgiving Attitude and Psychological Adjustment in Women with Breast Cancer

Abstract: The purpose of this study was to examine relationships among self-blame for developing breast cancer, a self-forgiving attitude, mood, and quality of life among women with breast cancer. In this cross-sectional study, 123 women with Stages 0-III breast cancer completed questionnaires measuring demographic and medical characteristics, self-blame, self-forgiveness, mood, and quality of life. Women who blamed themselves reported more mood disturbance (p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 33 publications
3
45
0
6
Order By: Relevance
“…We found that a more selfforgiving attitude was related to less mood disturbance and a better QoL which is consistent with what was found by Romero et al and Friedman et al [17,18]. We also found that a greater level of spirituality was associated with a reduced likelihood of mood disturbance and better QoL.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that a more selfforgiving attitude was related to less mood disturbance and a better QoL which is consistent with what was found by Romero et al and Friedman et al [17,18]. We also found that a greater level of spirituality was associated with a reduced likelihood of mood disturbance and better QoL.…”
Section: Discussionsupporting
confidence: 91%
“…Romero et al found a positive relationship between self-forgiveness and psychological adjustment in a predominantly African American and Hispanic sample of low-income women with breast cancer [17]. A similar relationship was found in a predominantly Caucasian sample of women with breast cancer in a private sector breast clinic [18]. It is possible that women who are more self-forgiving are less likely to blame themselves for developing breast cancer, and consequently experience less mood disturbance and enhanced QoL.…”
Section: Introductionmentioning
confidence: 79%
“…Selfblame is not a new concept in chronic disease management. [51][52][53][54][55][56][57] Self-blame may be an unintended consequence of the emphasis on patients' increased involvement in chronic disease management and their accepting greater responsibility for self-care. For patients with chronic conditions other than diabetes, self-blame is associated with poor psychological adjustment, depressive symptoms, and ineffectual coping.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with chronic conditions other than diabetes, self-blame is associated with poor psychological adjustment, depressive symptoms, and ineffectual coping. 53,[56][57][58] In diabetes, self-blame may result from challenges managing the complex self-care regimen along with the potential for poor treatment outcomes, which can amplify a sense of failure and lead to self-blame. 54,59 In our study, patients described feeling a sense of personal failure when not achieving treatment goals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that these distinct viewpoints may be supported by observations that, for affected women, thinking about the possible causes of one's cancer may be driven by emotional processes as opposed to a logical or rational approach [20]. Some research suggests that breast cancer patients who attributed their cancer to behavioral choices experienced negative emotional states and poorer quality of life [21,22].…”
mentioning
confidence: 99%